Fatwa Majelis Ulama Indonesia tentang Pernikahan Beda Agama: Studi Pemikiran Syariat Islam di Indonesia - R. Abdullah (Institut Islam Nahdlatul Ulama Temanggung, 2017)
Majlis Ulama Indonesia has issued a fatwa on interfaith marriage on June 1, 1980. The fatwa stipulates: 1. That an Islamic woman is not allowed (haram) to be married to non-Muslim men, 2. That a Muslim man is not allowed marry a non-Muslim woman. This fatwa was then reinforced by the decision of Fatwa Majlis Ulama Indonesia Number 4 / MUNAS VII / MUI / 8/2005, dated July 28, 2005, stating that the Marriage of different religions is haram and illegitimate, marriage of Muslim men with women scribes according to qaul mu’tamad is haram and illegitimate. The fatwa is interesting, because although the Qur’an clearly allows a Muslim man to marry a woman from a scribe, the fatwa does not allow it. Fatwa of such marriage ban because of its loss (mafsadah) is greater than the benefits (maslahah). Although this fatwa is specifically directed to events in Indonesia; but it is radical because it contradicts what is clearly stated in Qur’an. The fatwa is also against the classical Jurisprudence books, usually referred to by Majlis Ulama Indonesia in making other fatwas. The classical Jurisprudence texts agree to grant permission to Muslim men to marry women of the scribes. The issue of a fatwa by Majlis Ulama Indonesia which forbids Muslims and men from marrying non-Muslims, even those of the scribes, is apparently motivated by the conviction of religious rivalry and that the rivalry is considered by scholars to have reached a point of vulnerability for the interests and growth of the Muslim community. In addition, in the midst of society there have been thoughts that justify the marriage of different religions under the pretext of human rights and welfare, so that the door to the possibility of interfaith marriage should be completely closed.